Global Mamas: confronting the challenges of marketing fair trade apparel to female millennials. (5th March 2021) - VanderPloeg, Alyson; Domina, Tanya; Lee, Seung-Eun
This case presents to students the challenges that Global Mamas, a fair trade non-profit organisation, is experiencing in marketing its products to female millennials. Research has indicated that female millennials have a significant interest in purchasing fair trade products; however, there are a number of concerns that have prevented fair trade products from gaining mainstream acceptance among this consumer group. First, the case defines fair trade and discusses the growing niche market surrounding it. Second, Global Mamas is introduced and its current marketing, production, and distribution strategies are examined, as well as the current challenges Global Mamas is facing in capturing the attention and gaining the loyalty of this growing niche market. Students will be able to explain the foundational principles of fair trade and develop potential marketing strategies intended for the industry's niche market, addressing concerns they have regarding fair trade products and labelling procedures.